Isolation of DNA from archival Papanicolaou stained cytological smears using a simple salting-out procedure. Issue 1 (February 1995) - Poljak, M; Barlič, J; Seme, K; Avšič-Županc, T; Zore, A
Abstract : DNA from archival Papanicolaou stained and unstained cytological smears was successfully isolated using a simple, rapid and inexpensive salting-out procedure. The quality of DNA was controlled by polymerase chain reaction (PCR) amplification of segments of the human β-globin, human β-actin and human papillomavirus L1 genes. Only negligible differences in amplification efficiency were observed between DNA isolated from stained and unstained smears. The salting-out procedure is a more rapid method for the isolation of DNA than phenol-chloroform extraction and may be used in instances where fresh or cryopreserved clinical specimens are not available.